8y³+27z³ simply using suitable Identity
Answers
Answered by
1
Hey mate!!
Here is your answer!!
(2y)^3 + (3z)^3
Using identity a^3+b^3 = (a+b) (a^2-ab+b^2)
So,
(2y+ 3z) (4y^2-6ab+9z^2)
Hope it helps!!
Pls mark me as brainliest!!
Here is your answer!!
(2y)^3 + (3z)^3
Using identity a^3+b^3 = (a+b) (a^2-ab+b^2)
So,
(2y+ 3z) (4y^2-6ab+9z^2)
Hope it helps!!
Pls mark me as brainliest!!
Answered by
0
Answer:
2y⁴ - 6y³z + 6yz³ - 9z⁴
Step-by-step explanation:
= 2³y³ + 3³z³
= (2y)³ + (3z)³
= (2y + 3z)³ (2y - 3z)³
= 2y³(2y -3z) + 3z³(2y - 3z)
= 2y⁴ - 6y³z + 6yz³ - 9z⁴
Similar questions